Association of P2X7R gene with serum lipid profiles in Chinese postmenopausal women with osteoporosis. (3rd September 2019) - Xiao, W.; Gong, C.; Liu, X.; Liu, Y.; Peng, S.; Luo, D.; Wang, R.; Li, T.; Zhao, J.; Xiong, C.; Liang, S.; Xu, H.
Abstract: Objectives: The aim was to study the relationship between purinergic P2X7 receptor ( P2X7R ) functional genetic polymorphisms and lipid profiles in Chinese postmenopausal osteoporosis (OP) patients and controls. Methods: A total of 517 OP patients and 531 controls were randomly recruited by cluster sampling; blood was drawn to analyze P2X7R genetic polymorphisms and serum lipid levels. Bone mineral density (BMD) at the lumbar spine and hip was measured via dual-energy X-ray absorptiometry. Results: P2X7R rs2230911 was found to be associated with serum total cholesterol, triglyceride (TG), high-density lipoprotein (HDL), low-density lipoprotein, and BMD at the lumbar spine and hip in OP patients ( p  < 0.05). P2X7R rs3751143 was shown to be associated with serum TG and hip BMD in OP patients ( p  < 0.05). Furthermore, their estimated haplotype (rs1718119G-rs2230911C-rs3751143A) was indicated to be associated with TG, HDL, and BMD at the lumbar spine and hip in OP patients. However, no difference in the level of lipid profiles or BMD was found to be related to P2X7R genotype or haplotype in the control group ( p >0.05). Conclusions: Our findings suggest that P2X7R functional genetic polymorphisms and their estimated haplotypes are associated with serum lipid concentrations and BMD among Chinese postmenopausal women with OP.